2010
DOI: 10.4141/cjas09046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of presynchronization and postinsemination treatments on pregnancy rates to a timed breeding Ovsynch protocol in dairy cows and heifers

Abstract: Gordon, M. B., Dinn, N. and Rajamahendran, R. 2010. Effects of presynchronization and postinsemination treatments on pregnancy rates to a timed breeding Ovsynch protocol in dairy cows and heifers. Can. J. Anim. Sci. 90: 35Á44. This study examined two strategies to improve pregnancy rate (PR) following Ovsynch timed artificial insemination (TAI) for lactating dairy cows (n0225) and nulliparous heifers (n 087). Animals were assigned randomly to receive one of three treatments: Ovsynch protocol (GnRH 7 d before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Larsson and Berglund (2000) found a decrease in the number of AI per conception (1.6 vs 1.9) and a tendency for improved first AI conception rate (56 vs. 49%) between cows bred for a 15-mo and for a traditional 12-mo calving interval (Larsson and Berglund, 2000). Gordon et al (2010) reported that the efficiency of Ovsynch increases if the protocol is initiated between 76 to 105 DIM compared with 60 to 75 DIM. The positive effect of an extension of the VWP on the reproductive efficiency of cows timed inseminated after synchronization is further supported from the results of Stangaferro et al (2018).…”
Section: Discussionmentioning
confidence: 98%
“…Larsson and Berglund (2000) found a decrease in the number of AI per conception (1.6 vs 1.9) and a tendency for improved first AI conception rate (56 vs. 49%) between cows bred for a 15-mo and for a traditional 12-mo calving interval (Larsson and Berglund, 2000). Gordon et al (2010) reported that the efficiency of Ovsynch increases if the protocol is initiated between 76 to 105 DIM compared with 60 to 75 DIM. The positive effect of an extension of the VWP on the reproductive efficiency of cows timed inseminated after synchronization is further supported from the results of Stangaferro et al (2018).…”
Section: Discussionmentioning
confidence: 98%
“…In the sensitivity analysis, there were not any discrepancies neither in the differences between treatments nor in the hierarchy of treatments. Also another sensitivity analysis was performed by excluding those studies, or subgroups within studies, which are conducted with heifers and we did not observe any notable difference in results (King and Robertson, 1974;Stevenson et al, 2000Stevenson et al, , 2008Iwakuma et al, 2008;Karakas et al, 2009;Nak et al, 2009;Gordon et al, 2010). In another sensitivity analysis that we performed excluding the studies published in Turkish journals in Turkish language, we did not encounter any different results compared to the primary model (Aksu, 2010;Bülbül and Ataman, 2005;Kaçar, 2008).…”
Section: Synthesis Of the Resultsmentioning
confidence: 71%
“…This study was conducted in a commercial dairy farm located in Ankara province (N39.32021, E32.91506). Animals were inseminated using fixed‐time artificial insemination followed by a presynch‐ovsynch synchronization program (Giordano et al, 2016; Gordon et al, 2010). To eliminate the bull/sperm effect on pregnancy, heifers and cows were inseminated with commercially available frozen bull semen from a single Holstein bull of known fertility, frozen at the same collection date.…”
Section: Methodsmentioning
confidence: 99%